A fluorescent probe for sequential sensing of MnO4− and Cr2O72− ions in aqueous medium based on a UCNS/TMB nanosystem. Issue 13 (14th March 2019) - Liu, Haiquan; Rong, Jianing; Shen, Guoqiong; Song, Yao; Gu, Wen; Liu, Xin
Abstract : Distinguishable and sequential detection of MnO4 − and Cr2 O7 2− was realized by the reactions above and IFE between UCNS and oxTMB. Abstract : This paper reports the successful design of an UC fluorescence nanosystem for distinguishable and sequential detection of MnO4 − and Cr2 O7 2− based on the inner filter effect (IFE) between Gd2 O3 :Yb, Er upconversion nanospheres (UCNS) and 3, 3′, 5, 5′-tetramethylbenzidine (TMB). The detection of MnO4 − was realized by a stoichiometric oxidation reaction between TMB and Mn(vii ), which resulted in quenching of the upconversion luminescence (UCL) by the blue product through IFE. The assay of Cr2 O7 2−, in contrast, was based on the formation of complexes and the consumption of the oxidation product of the previous reaction. The sensing of MnO4 − did not interfere with that of Cr2 O7 2− when Pb 2+ was added as a masking agent. This provides a new strategy for sensitive and selective detection of MnO4 − and Cr2 O7 2− . The detection of MnO4 − showed not only a low LOD of 0.243 μM but also high selectivity over other possible interfering ions. The sensitivity assay of MnO4 − can be performed in the linear range of 1.85 to 69 μM. An excellent linear relationship was also found in the sensing of Cr2 O7 2−, with a linear range of 18.3 to 250 μM and a LOD of 2.95 μM. The selectivity towards Cr2 O7 2− was also proved to be good. Based on these properties, the UCNS–TMB nanoplatform is a potential chemosensor for both MnO4 − and Cr2 O7 2− ions in practical assays for waste water.